Fungsi Dewan Perwakilam Rakyat Dalam Pembentukan Peraturan Daerah - Sikafir, Beregita Lidiana; Nirahua, Salmon Eliazer Marthen; Pietersz, Jemmy Jefry (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: Article 1 paragraph 3 of the Republic of Indonesia Constitution provides legal guarantees. The Indonesian state in its government system has developed in terms of state institutions which we usually know as decentralization, the presence of the DPRD as a legislative institution or people's representative institution has the task of regulating regional government. Law Number 23 of 2014 concerning Regional Government, the DPRD has duties and authorities at the provincial and district/city levels, one of which is forming regional regulations.Purposes of the Research: This study aims to etermine the whether the function of forming regional regulations is an obligation for the DPRD, and the legal consequences if the function of forming regional regulations is not carried out by the DPRD.Methods of the Research: This study use normative juridical research, which to find out whether the function of forming regional regulations is an obligation for the DPRD, and the legal consequences if the function of forming regional regulations is not carried out the DPRD.Results of the Research: unction forming regional regulations as obligation of the DPRD is regulated in Law No. 23 of 2014 concerning Regional Government. in making regional regulations, authority is given by Bapemperda whose authority regulated by Article 52 PP No. 12 of 2018 concerning Guidelines for Preparing Provincial, Regency, City DPRD tatips. Bapemperda in exercising its authority to form regional regulations is outlined in the Propemperda. The authority given by this law is expected that the DPRD can understand its function an obligation. Among them is the function of forming regional regulations as an obligation of the DPRD. legal consequences for the DPRD not carrying out the function of forming regional regulations based on the problems raised by the author are that there are legal sanctions for the DPRD.